People in my neighborhood - Lyons, Shelly (North Mankato, Minn. : Capstone Press, 2013)
Describes some of the people in a neighborhood who help, teach, or serve.
Who are your neighbors? -- Helping neighbors -- Neighbors who teach -- Neighbors who serve.
School Library Journal, April 2013
Booklist, June 2013
Includes bibliographical references (p. 23) and index.
1.7
K-3
Center for the Collaborative Classroom Curriculum.
Keywords: Neighborhoods -- Juvenile literature; Neighbors -- Juvenile literature; Neighborhoods; Neighbors; Readers (Elementary)